Organizational Culture and Organizational Innovation Capability through the Mediation of Knowledge Sharing - Mufidah, Luthfiah; Tania, Ken Ditha (Universitas Negeri Semarang, 2024)
This research aims to explore the enhancement of the organizational innovation capability (OIC) in the South Sumatra Balitbangda through the role of organizational culture (OC), with the help of knowledge sharing (KS) as an intervening variable to help South Sumatra Balitbangda, which is a supporting element of the government responsible for government innovation in the South Sumatra region, maximize their competence in innovation capability. This research uses a quantitative approach with census sampling method which covers all of Balitbangda’s active employees. The examination of the collected data uses the PLS-SEM method with a total of 53 valid questionnaire responses from Balitbangda’s employees. The results indicate that OC and KS positively and significantly influence enhancing OIC. It has also proved that KS effectively mediates the relationship between OC and OIC. This study suggests a bigger sample size and scope, and the exploration of other potential variables in enhancing innovation capabilities for future research.